Quali-Quantitative Analysis (QQA): Why It Could Open New Frontiers for Holistic Health Practice - Erica Bell (The Scientific World Journal)
Holistic health practice is often described as being about understanding the larger contexts of patients, their health services, and their communities. Yet do traditional quantitative and qualitative health research methods produce the best possible evidence for the holistic practices of doctors, nurses, and allied health professionals? This paper argues “no”, and examines the potential of a cutting-edge, social science research method — Quali-Quantitative Research (QQA) — for providing better evidence for holistic practice, particularly in small-N populations, such as rural and remote communities. It does so with reference to the international literature on holistic medicine, as well as three holistic health projects conducted in Tasmania: about prevention of falls in older people, adolescent substance abuse, and interventions for children aged 05 exposed to domestic violence. The findings suggest that much health research fails to capture rigorously the contextual complexity of holistic health challenges: the multiple different needs of individual patients, and the interprofessional approaches needed to deliver multidisciplinary and multiservice health interventions tailored to meet those needs in particular community contexts. QQA offers a “configurational”, case-based, diversity-oriented approach to analysing data that combines qualitative and quantitative techniques to overcome the limitations of both research traditions. The author concludes that QQA could open new frontiers for holistic health by helping doctors, nurses, and allied health professionals answer a fundamental question presented by complex health challenges: “Given this set of whole-of-patient needs, what elements of which interventions in what services would work best in this particular community?”